Laparoscopic Management of Concomitant Sigmoid Colon Cancer and Type 2 Endoleak Following Endovascular Aneurysm Repair. (July 2022) - Bakopoulos, Anargyros; Koliakos, Nikolaos; Papaconstantinou, Dimitrios; Bistarakis, Dimitrios; Zymvragoudakis, Vassilios; Schizas, Dimitrios; Pikoulis, Emmanouil; Lazaris, Andreas M.
The co-occurrence of abdominal aortic aneurysm (AAA) and colorectal malignancy creates a significant surgical dilemma over which entity should be addressed first. A 73-year-old male was referred to our hospital due to a painful pulsatile abdominal mass. Computed tomographic angiography revealed an infrarenal aortic aneurysm measuring 5.8 cm in diameter and incidentally, a synchronous mass lesion in the sigmoid colon. The patient underwent an emergency EVAR using a Gore Excluder endograft. Postoperative CT staging for colon cancer revealed a type 2 endoleak on the grounds of a patent wide inferior mesenteric artery. The patient underwent a standard laparoscopic left colectomy with high ligation of the inferior mesenteric artery in order to simultaneously address the ongoing type 2 endoleak. Follow-up examinations with computed tomographic angiography were performed confirming the resolution of the endoleak. Synchronous laparoscopic sigmoidectomy and high ligation of inferior mesenteric artery for type 2 endoleak treatment appears to be applicable with hopeful results.